Effective reduced graphene oxide sheets/hierarchical flower-like NiO composites for methanol sensing under high humidity - Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Fonseca, Cristiane S. [UNESP]; Volanti, Diogo P. [UNESP] (My University, 2018)
Recent advances in NiO-based gas sensors have been reported, but high working temperatures and dry conditions are usually required. Herein, we report the volatile organic compound (VOC) sensing performance of flower-like (FL) NiO hierarchical structures modified with reduced graphene oxide (RGO) sheets under high humidity. RGO/FL-NiO composites were synthesized by a simple and template-free microwave-assisted hydrothermal method and subsequent calcination at 250 °C. The VOC-sensing properties were investigated for several VOCs, such as acetone, ethanol, methanol, m-xylene, and toluene, at 90% relative humidity. The RGO/FL-NiO composites exhibited a decrease in the optimal operating temperature and enhanced methanol responses compared to pure FL-NiO. In addition, the 5% RGO/FL-NiO composite exhibited the highest response of 61.51% to 100 ppm of methanol at 180 °C, which was 1.4-9.9 times superior to responses to other VOCs, indicating the sensor's great selectivity. The improved methanol sensing properties could be attributed to the NiO/RGO heterointerface.